Does Remediation Work for All Students? How the Effects of Postsecondary Remedial and Developmental Courses Vary by Level of Academic Preparation - Boatman, Angela; Long, Bridget Terry (Educational evaluation and policy analysis)
We examine the impact of remedial and developmental courses on college students with varying levels of academic preparedness, thus focusing on a wider range of students than previous studies. Using a regression discontinuity design, we provide causal estimates of the effects of placement in different levels of remedial courses on short-, intermediate-, and long-term outcomes at both 2- and 4-year colleges. Similar to other research, we find that remediation has negative effects for students on the margin of needing one developmental course. However, for students with lower levels of academic preparation, the effects of remediation are estimated to be positive in some subjects. These results suggest that remedial courses can help or hinder students differently depending on their incoming levels of academic preparedness. Moreover, our conclusions are largely driven by positive and negative effects observed for students at 2-year institutions, and we discuss several hypotheses that may explain these findings.